The feeling of quality of life and its relation to the optimistic or pessimistic perspective and its impact on mental health - Khermouche, Samira (Journal of Human Sciences, 2023)
In This article, we discuss the following concepts: optimism, pessimism, mental health and quality of life as interdependent concepts, highlighting their theoretical content and focusing on their common aspects and their impact on social life of the individual. He also analyzed and explained the fundamental relationship between the three variables and their importance by presenting a set of studies dealing with these variables. The article concluded that there is a relationship between the three variables.